Differential distribution of plasma apoA-I and apoB levels and clinical significance of apoB/apoA-I ratio in ischemic stroke subtypes - Van Tuyen, Nguyen; Hoang Ngoc, Nguyen; Quoc Hoan, Phan; Thi Yen, Nguyen; Hoan, Nghiem Xuan; Cam Thach, Nguyen (Frontiers in Neurology, 2024)
Background and purpose Ischemic stroke (IS) is classified into clinical subtypes and likely influenced by various lipid components. Nevertheless, the roles of apolipoprotein A-I (apoA-I), apolipoprotein B (apoB), and apoB/apoA-I ratio in different IS subtypes remain underexplored. This study aimed to investigate the differential distribution of plasma apoA-I and apoB levels among IS subtypes and to evaluate the predictive value of the apoB/apoA-I ratio in assessing IS subtypes and disease severity. Methods In this study, 406 IS patients were categorized into three IS-subtypes based on clinical manifestations and imaging assessment, including intracranial atherosclerosis-related IS patients (ICAS, n = 193), extracranial atherosclerosis-related IS patients (ECAS, n = 111), and small artery occlusion-related IS patients (SAO, n = 102). Plasma apoA-I and apoB levels were measured upon hospital admission. Random forest (RF) models were performed to assess predictive values of these apolipoproteins apoB, apoA-I and their ratio in assessing IS subtype stratification and disease severity. Results Serum apoA-I levels were significantly lower in ICAS compared to ECAS and SAO patients (p < 0.0001), while apoB levels were higher in ICAS patients (p < 0.0001). The apoB/apoA-I ratio was significantly higher in ICAS compared to ECAS and SAO patients (p < 0.0001). Correlation analyses found a significant correlation between the apoB/apoA-I ratio and conventional lipid components. Additionally, RF models and plots of variable importance and distribution of minimal depth revealed that the apoB/apoA-I ratio played the most influential predictor in predicting IS subtypes and stenosis severity. Conclusion Our study shows the differential distribution of apoA-I and apoB IS subtypes and reveals the significance of the apoB/apoA-I ratio in assessing IS subtypes and arterial stenosis severity. Further studies are warranted to validate these findings and enhance their clinical applicability.